Pola Suku Kata Bahasa Molof - Yohanis Sanjoko (Balai Bahasa Provinsi Papua, 2019)
Parts of words spoken in one breath, usually consisting of several phonemes which is a syllable. Molof syllables has always a core vowel syllables. Molof syllables consisting of one vowel, one vowel and one consonant, a consonant and a vowel, and one consonant, one vowel, and one consonant.